2015
DOI: 10.1111/1540-6229.12104
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mortgage Payment Reduction on Default: Evidence from the Home Affordable Refinance Program

Abstract: This article evaluates the effect of payment reduction on mortgage default within the context of the Home Affordable Refinance Program. We find that mortgage default is sensitive to payment reduction using univariate, duration and hazard modeling approaches. A relative risk Cox model of default with time‐varying covariates estimates that a 10% reduction in mortgage payment is associated with about a 10–11% reduction in monthly default hazard for loans. This finding is robust to the inclusion of empirically imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In Equation ( 7), i ε is an i.i.d. random variable that satisfies the log-Weibull distribution and σ is a scale parameter, and since Weibull AFT is a parametric AFT model, the expected survival time can be derived as Equation (8), which can give a clear indication how covariates impact survival time ( [19]).…”
Section: ( )mentioning
confidence: 99%
See 1 more Smart Citation
“…In Equation ( 7), i ε is an i.i.d. random variable that satisfies the log-Weibull distribution and σ is a scale parameter, and since Weibull AFT is a parametric AFT model, the expected survival time can be derived as Equation (8), which can give a clear indication how covariates impact survival time ( [19]).…”
Section: ( )mentioning
confidence: 99%
“…First, [7] used the Cox model, found a high net property value, and a high house price growth rate decreased mortgage default. Second, [8] researched the effect of mortgage monthly payment paydown on mortgage default using a Cox Proportional Hazards model, and discovered that a high percentage of monthly paydown reduces the risk of mortgage default. Finally, [9] found that the origi- To compare the accuracy of the models, training and test data will be constructed and a C-index will serve as the accuracy metric, and the motivating factor for using C-index as the performance metric is because for incomplete data, accuracy could not be defined.…”
Section: Introductionmentioning
confidence: 99%
“…In our next paper, Zhu et al . () examine the relationship between HARP‐related payment reductions and mortgage defaults using various statistical methods. For Freddie Mac borrowers that refinanced from one 30‐year fixed rate mortgage to another, the authors find that a 10% reduction in mortgage payments was associated with a 10–11% reduction in default propensity.…”
Section: Government Responses To the Housing Crisismentioning
confidence: 99%
“…Since we use market-wide data, we also allow for "cross-GSE" refinances (e.g. from Freddie Mac to Fannie Mae), or cases where the new loan remains in the lender's portfolio.3 Another related study is byZhu et al (2015), who use Freddie Mac mortgages likeKaramon et al (2016) but focus primarily on the "intensive margin," comparing HARP refinances with payment reductions of different size. They find that larger payment reductions result in lower default probabilities.4Agarwal et al (2017a) furthermore show that ZIP codes with more eligible borrowers see higher car sales, credit card spending, and house price growth, and lower foreclosures; this is consistent with HARP refinances having local aggregate effects.…”
mentioning
confidence: 99%